Maximum power exploitation for grid-connected PV system under fast-varying solar irradiation levels with modified salp swarm algorithm. (20th September 2020) - Mao, Mingxuan; Zhang, Li; Huang, Han; Chong, Benjamin; Zhou, Lin
Abstract: With the rapid development of photovoltaic (PV) power generation technology, PV generation system has been applied into planes, cars, boats and trains. Solar irradiation levels will change rapidly in these PV systems. Fast-varying solar irradiation can invalidate the traditional configurations of PV system and maximum power point tracking (MPPT) control strategy, which will reduce the energy conversion efficiency. In order to extract maximum power exploitation, this paper proposes a novel maximum power exploitation configuration combined with the proposed control scheme for grid-connected PV system under fast-varying solar irradiation levels. In the proposed configuration, each PV panel cascades a step-up boost converter, hence allowing independent control corresponding to the irradiation levels, which generates multiple-levels of dc-voltage and may be converted to ac via an active neutral point clamped (ANPC) inverter. Meanwhile, a modified salp swarm algorithm with dynamic w factor (DWSSA) based MPPT method is proposed for each boost converter units, which can effectively accelerate convergence velocity and stability of iteration to make the searching process rapidly adapting to different fast-varying solar irradiation levels. In order to express the dynamic variation of the PV system, the mathematical model of the proposed configuration is established. Moreover, the performance of the proposed DWSSA algorithm is investigated by the stability analysis based Lyapunov theory and convergence analysis on 23 benchmark functions and CEC 2005 benchmark functions. Finally, the constructed simulation test platform is implemented and the results demonstrate that the configuration can exploit the variable converter ratios, and the proposed DWSSA method has faster tracking speed and higher energy extraction efficiency compared with the previous MPPT methods in most cases, especially, the power extraction percentage of 97.89% and the tracking time of 0.761s under the most severe uneven solar irradiation levels. Graphical abstract: Image 1 Highlights: . The mathematical model of amaximum power exploitationconfigurationisbuilt；. . Afast-convergencesalpswarm algorithm based MPPT method is proposed. . Thestabilityanalysis based Lyapunov theoryisgivenforDWSSA. . Theconvergenceanalysisof 13algorithms on 38benchmark functionsisgiven. . The test platformis constructedto validatethe configurationwith DWSSA.